Silicon carbide powder as well as preparation method and application thereof
By using the combination technology of hollow nanosilicon dioxide and organic nickel salt, the problem of insufficient silicon source purity and reaction activity in the preparation of silicon carbide powder was solved, and high-purity and high-performance silicon carbide powder preparation was achieved, which improved its sintering performance and application effect.
Patent Information
- Application Number
- CN202411807414.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The preparation method of silicon carbide powder in the prior art has problems of insufficient purity and reactivity of silicon source, and the catalytic effect of metal salts is limited by compatibility problems.
Hollow nanosilicon dioxide is used as the silicon source, and organic nickel salt is added to the high-temperature reaction to improve the reactivity of the silicon source and the carbon source and the purity and performance of the silicon carbide powder.
Through the high-temperature calcination of hollow nanosilicon dioxide and the catalytic action of organic nickel salt, the precipitation speed and purity of silicon carbide powder are significantly improved, and its sintering performance and application effect are improved.
Smart Images

Figure CN119569070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic materials, and specifically relates to silicon carbide powder and a preparation method and application thereof. Background Art
[0002] Silicon carbide (SiC) is a strong covalent bond compound material with excellent properties such as high temperature resistance, wear resistance, corrosion resistance, radiation resistance, high hardness, high elastic modulus, high thermal conductivity, good high temperature strength, small thermal expansion coefficient, good thermal shock resistance, high critical breakdown electric field, high saturated electron drift velocity, small dielectric constant and good wave absorption performance. It has been widely used in many fields, especially in aerospace, machinery, metallurgy, energy, environmental protection, chemical industry, medicine, electronics, military industry and other high-tech fields. The two most common crystal forms of silicon carbide are α-SiC and β-SiC. β-SiC is a cubic crystal with a structure similar to diamond. Compared with hexagonal α-SiC, β-SiC has higher hardness (Mohs hardness of more than 9.5), better toughness and superior grinding performance, reinforcement and toughening functions; β-SiC has better sintering performance than α-SiC, and the finer the powder, the higher the sintering activity.
[0003] The preparation methods of silicon carbide powder in the prior art have the following problems: (1) Most of the silicon sources used are silicon dioxide or elemental silicon, which exist in two forms: crystalline and amorphous. The crystalline form has high purity but insufficient reactivity, while the amorphous form has high reactivity but insufficient purity. Therefore, it is necessary to provide silicon dioxide or elemental silicon with high purity and high reactivity. (2) When the prior art uses the carbon reduction method to prepare silicon carbide powder, the appropriate amount of metal salt (such as nickel salt, iron salt, etc.) can play a catalytic role in the reaction. However, the prior art has not considered the compatibility of metal salts in carbon sources and silicon sources, which affects the catalytic effect.
[0004] The prior art adopts the sol-gel method to prepare hollow nano-silica, which can produce silica with a high specific surface area. However, the template molecules (such as calcium carbonate, polystyrene, etc.) are not completely removed, resulting in insufficient purity of the hollow nano-silica. This is because most of the prior art only considers its adsorption performance, and does not consider its reactivity and purity required as a reaction material.
[0005] In summary, how to provide a silicon carbide powder and a preparation method and application thereof, so as to improve the reaction activity in the preparation process of the silicon carbide powder while also improving the purity and performance of the silicon carbide powder, is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a silicon carbide powder and a preparation method and application thereof. The present invention uses hollow nano-silicon dioxide as a silicon source, which can improve the reaction activity of the silicon source and the carbon source. The hollow nano-silicon dioxide forms liquid silicon faster during the high-temperature reaction process, which accelerates the precipitation of silicon carbide. In addition, an organic nickel salt is added, and the organic part of the substance can serve as a partial carbon source. The nickel element can catalyze the reaction between carbon and silicon dioxide, thereby comprehensively improving the purity and performance of the silicon carbide powder.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing hollow nano-silica comprises the following steps: Add cationic compounds to a suspension of nano calcium carbonate (50-100nm), adjust the solution pH to 9-10, then heat to 40-80℃ and stir for 10-60min, then slowly add sodium silicate solution under stirring, age for 2-5h, filter, wash, dry at 100-120℃, calcine at 300-600℃ for 3-5h, finally dissolve impurities with hydrochloric acid, filter, wash, and dry to obtain hollow nano silica. The cationic compound is acetylglutamide aluminum.
[0008] Preferably, the amount of the cationic compound added is 0.5-1.5% of the mass of the nano-calcium carbonate.
[0009] Preferably, the mass concentration of the nano-calcium carbonate suspension is 60-100 g / L, the mass concentration of silicon dioxide in the sodium silicate solution is 3-10%, and the mass ratio of sodium silicate solution to nano-calcium carbonate is 12-30% in terms of silicon dioxide / calcium carbonate.
[0010] The present invention also provides a method for preparing silicon carbide powder, which adopts the reaction of a carbon source and a silicon source, wherein the silicon source is the hollow nano-silicon dioxide prepared by the above method, and the method for preparing silicon carbide powder comprises the following steps: The hollow nano-silicon dioxide is dried to obtain dry powder, and the dry powder and carbon powder (50-500nm) are placed in an inert atmosphere (helium or argon) for calcination. After the calcination is completed, carbon is discharged at 600-800°C for 40-80min, and finally the temperature is lowered to room temperature at a rate of 8-20°C / min to obtain silicon carbide powder; the crystal form of the silicon carbide powder is β-SiC.
[0011] Preferably, an organic nickel salt is further added to the method for preparing the silicon carbide powder. In this case, the method for preparing the silicon carbide powder specifically comprises the following steps: The hollow nano-silicon dioxide is soaked in an organic nickel salt aqueous solution for 10-60 minutes, and then the water is evaporated to obtain a dry powder. The dry powder and carbon powder (50-500nm) are calcined under an inert atmosphere (helium or argon). After the calcination is completed, carbon is discharged at 600-800°C for 40-80 minutes, and finally the temperature is cooled to room temperature at a rate of 8-20°C / min to obtain silicon carbide powder. The crystal form of the silicon carbide powder is β-SiC.
[0012] The organic nickel salt is specifically ethylenediaminetetraacetic acid disodium nickel salt, nickel oxalate or nickel acetate, preferably ethylenediaminetetraacetic acid disodium nickel salt.
[0013] Preferably, the molar ratio of the hollow nano-silicon dioxide to the carbon powder is 1:(1-1.2) in terms of silicon / carbon, and the molar ratio of the hollow nano-silicon dioxide to the organic nickel salt is 1:(0.02-0.1) in terms of silicon / nickel.
[0014] Preferably, the calcination temperature is 1300-1600° C., the heating rate is 5-10° C. / min, and the calcination time is 1-3 h.
[0015] Preferably, after carbon removal, the powder is further impurity-removed by using any one or two of acid washing and alkali washing, the acid is one or more of hydrochloric acid, hydrofluoric acid, sulfuric acid, and nitric acid, the alkali is one or more of sodium hydroxide, potassium hydroxide, and ammonia water, and the mass concentration of the acid and the alkali is 10-30%.
[0016] Preferably, the method for preparing the silicon carbide powder further comprises exhausting the dry powder before calcination, wherein the exhausting is as follows: heating the dry powder to 200-400°C in a flowing inert atmosphere (helium or argon) at a rate of 6-15°C / min, and keeping the temperature for 5-30 minutes.
[0017] The invention also provides an application of silicon carbide powder as a ceramic material.
[0018] Technical effects of the present invention: 1. The present invention adopts a carbon reduction method to prepare silicon carbide powder, and uses hollow nano-silicon dioxide as a silicon source, which can improve the reaction activity of the silicon source and the carbon source. The hollow nano-silicon dioxide forms liquid silicon faster during the high-temperature reaction process, which accelerates the precipitation of silicon carbide.
[0019] 2. When the present invention uses nano calcium carbonate as a template to prepare hollow nano silica, a cationic compound is also added, which can not only adhere to the surface of calcium carbonate (negatively charged under alkaline conditions) to form a positively charged structural layer, but also can react with sodium silicate to form a negatively charged silica gel adsorbed to promote the formation of silica on the surface of calcium carbonate.
[0020] The cationic compound of the present invention is preferably acetylglutamide aluminum, which contains polynuclear hydroxyl bridge aluminum ions. When added to the nano calcium carbonate suspension, it can also condense on the surface of calcium carbonate to improve the rheological properties of the nano calcium carbonate suspension, thereby promoting the coating of calcium carbonate by silicon dioxide and improving the coating rate.
[0021] 3. During the high-temperature calcination process of the hollow nano-silica prepared by the present invention, acetylglutamide aluminum can produce porous activated alumina, which can be used as a template to promote the formation of a porous structure in the inner pore wall of the hollow nano-silica. Acetylglutamide aluminum can also reinforce the strength of the inner layer of the hollow structure and improve the structural stability.
[0022] Compared with other cationic compounds (such as cationic surfactants), which are easily removed by high-temperature roasting to form carbon residues, thereby reducing the purity of hollow nano-silica, the acetylglutamide aluminum of the present invention can be dissolved together with calcium carbonate by hydrochloric acid without carbon residues. In addition, the presence of acetylglutamide aluminum can make the removal of calcium carbonate more complete, thereby reducing the amount of calcium carbonate remaining in the pores of the hollow particles.
[0023] 4. When preparing silicon carbide powder, the present invention also adds organic nickel salt. The organic part of the substance can serve as a partial carbon source, and the nickel element can catalyze the reaction between carbon and silicon dioxide, and it only takes 1-3 hours to fully react.
[0024] The organic nickel salt of the present invention is preferably nickel disodium ethylenediaminetetraacetate, which has the following functions: 1. It contains more active groups and can be attached to the surface of hollow nano-silica to improve the dispersibility of silicon dioxide powder and nickel salt in carbon powder, and avoid powder agglomeration or adhesion; 2. When the hollow nano-silica is immersed in a nickel salt aqueous solution, more nickel disodium ethylenediaminetetraacetate can be adsorbed, so that the hollow nano-silica acts as a catalytic carrier, and the catalytic activity of nickel is further improved; 3. Nickel disodium ethylenediaminetetraacetate is carbonized and releases small molecules at high temperature, which plays a role of supporting the hollow structure of the hollow nano-silica, and prevents the hollow structure from being destroyed before the temperature is raised to the calcination temperature, thereby maintaining the reaction activity of the hollow nano-silica; 4. Nickel disodium ethylenediaminetetraacetate is adsorbed in the hollow nano-silica, and the amorphous carbon formed after the high-temperature carbonization can react quickly and fully with silicon dioxide, and promote the formation of silicon carbide.
[0025] 5. When preparing silicon carbide powder in the present invention, there is a lot of air in the hollow structure of the hollow nano-silicon dioxide used. Although the calcination reaction under an inert atmosphere is not easy to affect the purity of the silicon carbide product, the organic nickel salt adsorbed in the hollow structure is easily oxidized by this part of air during the initial heating process, affecting the catalytic activity of the organic nickel salt. Therefore, the hollow nano-silicon dioxide needs to be exhausted before the calcination reaction.
[0026] Compared with conventional vacuum exhaust that easily causes pressure on the hollow structure of hollow nano-silica and causes damage, the present invention performs mild exhaust treatment on the hollow nano-silica in a flowing inert atmosphere before calcination, and decomposes part of the nickel disodium ethylenediaminetetraacetate into small molecular gases by heating. These small molecular gases form a rapid outward airflow when heated, which promotes the replacement of the air in the hollow structure of the silica by the external inert atmosphere, thereby improving the exhaust effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electron microscope scanning image of the silicon carbide powder prepared by the present invention; Figure 2 The XRD spectrum of silicon carbide powder prepared in the present invention. DETAILED DESCRIPTION
[0028] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0029] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art. Example 1
[0030] This embodiment provides a method for preparing silicon carbide (β-SiC) powder, which uses a carbon source and a silicon source to react, and the silicon source is hollow nano-silicon dioxide. The method for preparing the hollow nano-silicon dioxide includes the following steps: Add cationic compound (acetylglutamide aluminum, added in an amount of 1% of the mass of nano calcium carbonate) to a suspension of nano calcium carbonate (50nm) with a mass concentration of 80g / L, adjust the solution pH to 9.5, then heat to 60°C and stir for 30min, then slowly add sodium silicate solution (containing 6% mass concentration of silicon dioxide) under stirring conditions, age for 3h, filter, wash, dry at 110°C, calcine at 450°C for 4h, finally dissolve impurities with hydrochloric acid, filter, wash, and dry to obtain hollow nano silica. The mass ratio of sodium silicate solution to nano calcium carbonate is 20% according to silicon dioxide / calcium carbonate.
[0031] The preparation method of β-SiC powder comprises the following steps: The hollow nano-silica was soaked in an organic nickel salt (ethylenediaminetetraacetic acid disodium nickel salt) aqueous solution for 30 minutes, and then the water was evaporated to obtain a dry powder. The dry powder and carbon powder (50nm) were calcined under an inert atmosphere (argon) at a calcination temperature of 1400°C, a heating rate of 7.5°C / min, and a calcination time of 2h. After calcination, carbon was removed at 700°C for 40 minutes, and finally cooled to room temperature at a rate of 14°C / min. After carbon removal, the powder was decontaminated, and acid washing (hydrochloric acid with a mass concentration of 10%), alkali washing (sodium hydroxide with a mass concentration of 15%), and dried to obtain β-SiC powder.
[0032] The molar ratio of the hollow nano-silica to the carbon powder is 1:1 in terms of silicon / carbon, and the molar ratio of the hollow nano-silica to the organic nickel salt is 1:0.06 in terms of silicon / nickel. Example 2
[0033] The difference between this embodiment and embodiment 1 is that the organic nickel salt in the preparation method of the β-SiC powder is nickel oxalate. Example 3
[0034] The difference between this embodiment and embodiment 1 is that the organic nickel salt in the preparation method of the β-SiC powder is nickel acetate. Example 4
[0035] The difference between this embodiment and embodiment 1 is that no organic nickel salt is added in the preparation method of β-SiC powder, and the preparation method comprises the following steps: The hollow nano-silica was dried to obtain dry powder, and the dry powder and carbon powder (50nm) were placed in an inert atmosphere (argon) and calcined at a temperature of 1400°C, a heating rate of 7.5°C / min, and a calcination time of 2h. After calcination, carbon was removed at 700°C for 40min, and finally cooled to room temperature at a rate of 14°C / min. After carbon removal, the powder was acid-washed (hydrochloric acid) to remove impurities and dried to obtain β-SiC powder.
[0036] The molar ratio of hollow nano-silicon dioxide to carbon powder is 1:1.2 in terms of silicon / carbon. Example 5
[0037] Based on Example 1, this embodiment provides a method for preparing silicon carbide (β-SiC) powder, which also includes exhausting the dry powder before calcination. The exhaust treatment is: heating the dry powder to 300°C in a flowing inert atmosphere (argon) at a rate of 10°C / min and keeping it warm for 15 minutes. Example 6
[0038] This embodiment provides a method for preparing silicon carbide (β-SiC) powder, which uses a carbon source and a silicon source to react, and the silicon source is hollow nano-silicon dioxide. The method for preparing the hollow nano-silicon dioxide includes the following steps: Add cationic compound (acetylglutamide aluminum, added in an amount of 0.5% of the mass of nano calcium carbonate) to a suspension of nano calcium carbonate (50nm) with a mass concentration of 60g / L, adjust the solution pH to 9, then heat to 40°C and stir for 60min, then slowly add sodium silicate solution (containing 3% mass concentration of silicon dioxide) under stirring, age for 2h, filter, wash, dry at 100°C, calcine at 300°C for 5h, finally dissolve impurities with hydrochloric acid, filter, wash, and dry to obtain hollow nano silica. The mass ratio of sodium silicate solution to nano calcium carbonate is 12% according to silicon dioxide / calcium carbonate.
[0039] The preparation method of β-SiC powder comprises the following steps: The hollow nano-silica was immersed in an organic nickel salt (nickel disodium ethylenediaminetetraacetic acid salt) aqueous solution for 10 minutes, and then the water was evaporated to obtain a dry powder. After the dry powder was degassed, it was calcined with carbon powder (50nm) in an inert atmosphere (argon) at a calcination temperature of 1300°C, a heating rate of 5°C / min, and a calcination time of 3h. After calcination, carbon was discharged at 600°C for 80 minutes, and finally cooled to room temperature at a rate of 8°C / min. After carbon discharge, the powder was decontaminated, and acid washing (hydrochloric acid with a mass concentration of 10%), alkali washing (sodium hydroxide with a mass concentration of 15%), and dried to obtain β-SiC powder.
[0040] The molar ratio of hollow nano-silica to carbon powder is 1:1.1 in terms of silicon / carbon, and the molar ratio of hollow nano-silica to organic nickel salt is 1:0.02 in terms of silicon / nickel.
[0041] The exhaust treatment of the dry powder is as follows: the dry powder is heated to 200° C. at a rate of 6° C. / min in a flowing inert atmosphere (argon) and kept at this temperature for 30 minutes. Example 7
[0042] This embodiment provides a method for preparing silicon carbide (β-SiC) powder, which uses a carbon source and a silicon source to react, and the silicon source is hollow nano-silicon dioxide. The method for preparing the hollow nano-silicon dioxide includes the following steps: Add cationic compound (acetylglutamide aluminum, the amount added is 1.5% of the mass of nano calcium carbonate) to the suspension of nano calcium carbonate (50nm) with a mass concentration of 100g / L, adjust the solution pH to 10, then heat to 80℃ and stir for 10min, then slowly add sodium silicate solution (containing 10% mass concentration of silicon dioxide) under stirring conditions, age for 5h, filter, wash, dry at 120℃, calcine at 600℃ for 3h, finally dissolve impurities with hydrochloric acid, filter, wash, and dry to obtain hollow nano silica. The mass ratio of sodium silicate solution to nano calcium carbonate is 30% according to silicon dioxide / calcium carbonate.
[0043] The preparation method of β-SiC powder comprises the following steps: The hollow nano-silica was immersed in an organic nickel salt (nickel disodium ethylenediaminetetraacetic acid salt) aqueous solution for 60 minutes, and then the water was evaporated to obtain a dry powder. After the dry powder was degassed, it was calcined with carbon powder (50nm) in an inert atmosphere (argon) at a calcination temperature of 1600°C, a heating rate of 10°C / min, and a calcination time of 1h. After calcination, carbon was discharged at 800°C for 60 minutes, and finally cooled to room temperature at a rate of 20°C / min. After carbon discharge, the powder was decontaminated, and acid washing (hydrochloric acid with a mass concentration of 10%), alkali washing (sodium hydroxide with a mass concentration of 15%), and dried to obtain β-SiC powder.
[0044] The molar ratio of hollow nano-silicon dioxide to carbon powder is 1:1.2 in terms of silicon / carbon, and the molar ratio of hollow nano-silicon dioxide to organic nickel salt is 1:0.1 in terms of silicon / nickel.
[0045] The exhaust treatment of the dry powder is as follows: the dry powder is heated to 400° C. at a rate of 15° C. / min in a flowing inert atmosphere (argon) and kept at this temperature for 5 minutes.
[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the silicon source for preparing silicon carbide powder is ordinary silicon dioxide without a hollow structure.
[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that the cationic compound used in the preparation process of the hollow nano-silica is hexadecyltrimethylammonium bromide.
[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the cationic compound used in the preparation process of hollow nano-silica is dodecyltrimethylammonium chloride.
[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that, during the preparation of hollow nano-silica, the amount of the cationic compound added is 0.2% of the mass of the nano-calcium carbonate.
[0050] Comparative Example 5 The difference between this comparative example and Example 1 is that, during the preparation of hollow nano-silica, the amount of the cationic compound added is 2.0% of the mass of the nano-calcium carbonate.
[0051] Comparative Example 6 The difference between this comparative example and Example 1 is that in the preparation method of silicon carbide powder, organic nickel salt is directly added, and the preparation method of silicon carbide powder comprises the following steps: hollow nano-silicon dioxide, organic nickel salt and carbon powder are calcined under an inert atmosphere (argon), the calcination temperature is 1400°C, the heating rate is 7.5°C / min, and the calcination time is 2h. After calcination, carbon is discharged at 700°C for 40min, and finally the temperature is reduced to room temperature at a rate of 14°C / min. After carbon discharge, the powder is decontaminated, and acid washing (hydrochloric acid with a mass concentration of 10%), alkali washing (sodium hydroxide with a mass concentration of 15%), and drying are performed in sequence to obtain β-SiC powder.
[0052] Comparative Example 7 The difference between this comparative example and Example 1 is that in the method for preparing silicon carbide powder, the molar ratio of hollow nano-silicon dioxide to disodium nickel ethylenediaminetetraacetic acid is 1:0.01 in terms of silicon / nickel.
[0053] Comparative Example 8 The difference between this comparative example and Example 1 is that in the method for preparing silicon carbide powder, the molar ratio of hollow nano-silicon dioxide to disodium nickel ethylenediaminetetraacetic acid is 1:0.12 in terms of silicon / nickel.
[0054] Comparative Example 9 The difference between this comparative example and Example 5 is that in the method for preparing silicon carbide powder, the temperature for exhaust treatment of the dry powder before calcination is 150°C.
[0055] Comparative Example 10 The difference between this comparative example and Example 5 is that in the method for preparing silicon carbide powder, the temperature for exhaust treatment of the dry powder before calcination is 450°C.
[0056] Comparative Example 11 The difference between this comparative example and Example 5 is that in the method for preparing silicon carbide powder, the heating rate of exhaust treatment of the dry powder before calcination is 3° C. / min.
[0057] Comparative Example 12 The difference between this comparative example and Example 5 is that in the method for preparing silicon carbide powder, the heating rate of exhaust treatment of the dry powder before calcination is 18° C. / min.
[0058] 1. Microstructure of silicon carbide powder prepared by the present invention The silicon carbide powder product obtained in Example 5 of the present invention was scanned by electron microscope, and the results showed that Figure 1 It can be seen that the particle size is about 50nm, the particle size distribution is uniform, and the appearance is good. The XRD spectrum of the product powder is shown in Figure 2 , it can be seen that the product is β-SiC powder.
[0059] 2. Effect of preparing hollow nano-silica by the present invention 1. Basic properties of hollow nano-silica The particle size, specific surface area and purity of the hollow nano-silica prepared in Example 1 and Comparative Examples 2-5 were measured respectively. The results are shown in Table 1.
[0060] Table 1
[0061] It can be seen from Table 1 that, compared with Comparative Examples 2-5, the hollow nano-silica prepared in Example 1 of the present invention has a smaller particle size, a larger specific surface area and a higher purity.
[0062] 2. Strength of hollow nano-silica The strength of the hollow nano-silica prepared in Example 1 and Comparative Examples 2-5 was measured respectively. The results are shown in Table 2.
[0063] The strength test method is: A quantitative amount of carbon hollow nano-silica powder to be tested was weighed, and a stirrer was started to stir at a stirring speed of 1000 rpm for 30 minutes. The powder breakage was observed with an optical microscope to test the strength of the carbon hollow nano-silica.
[0064] Table 2
[0065] It can be seen from Table 2 that, compared with Comparative Examples 2-5, the hollow nano-silica prepared in Example 1 of the present invention does not break after high-speed stirring, indicating that the hollow nano-silica has good strength and a relatively stable hollow structure, and can effectively maintain the catalytic carrier effect of the hollow nano-silica on the organic nickel salt.
[0066] 3. Viscosity of Nano Calcium Carbonate Suspension The viscosity of the nano-calcium carbonate suspensions in the process of preparing hollow nano-silicon dioxide in Example 1 and Comparative Examples 2-5 was measured respectively. The results are shown in Table 3.
[0067] Table 3
[0068] It can be seen from Table 3 that, compared with Comparative Examples 2-5, the viscosity of the nano calcium carbonate suspension in the process of preparing hollow nano silica in Example 1 of the present invention is lower, and the easier it is for calcium carbonate to disperse in the system, the better the coating effect of sodium silicate on calcium carbonate.
[0069] 3. Basic properties of silicon carbide powder prepared by the present invention 1. Yield and purity of silicon carbide powder The yield and purity of the silicon carbide powders obtained in Examples 1-7 of the present invention and Comparative Examples 1, 6-12 were measured. The results are shown in Table 4.
[0070] Table 4
[0071] As can be seen from Table 4, the yield of silicon carbide powder obtained in Examples 1-7 of the present invention is in the range of 81.9%-97.7%, and the purity is in the range of 96.2-99.8%, among which the yield and purity of Examples 5-7 are higher, with a yield of up to 97.7% and a purity of up to 99.8.
[0072] By comparing Examples 1-3, it can be seen that when the organic nickel salt in Example 1 is disodium ethylenediaminetetraacetic acid nickel salt, the yield and purity of silicon carbide powder are higher. By comparing Examples 1 and 4, it can be seen that adding organic nickel salt can significantly improve the yield and purity of silicon carbide powder.
[0073] On the basis of Example 1, Example 5 performs exhaust treatment on the dry powder before calcination, and as a result, the reaction yield and purity of silicon carbide are further improved.
[0074] Compared with Example 1, Comparative Example 1 uses ordinary silicon dioxide. Compared with Example 5, Comparative Examples 6-12 change the preparation steps of silicon carbide powder. As a result, the yield and purity of the silicon carbide powder prepared in Comparative Examples 1 and 6-12 decrease to varying degrees.
[0075] 2. Dispersion of all powders during the preparation of silicon carbide powder The dispersion of all powders during the preparation of silicon carbide powder in Examples 1-4 was observed. The results are shown in Table 5.
[0076] Table 5
[0077] The hollow nano-silicon dioxide and carbon powder used in the preparation process of the silicon carbide powder of the present invention are both nano-scale. If the powder particle size is too small, it is very easy to agglomerate, and the uneven dispersion affects the entire reaction. As shown in Table 5, compared with Examples 2-4, after the hollow nano-silicon dioxide is impregnated with disodium nickel salt of ethylenediaminetetraacetic acid in Example 1 of the present invention, the dispersion effect is significantly improved, which is beneficial to improving the preparation effect of silicon carbide powder.
[0078] 3. Free carbon content of the powder obtained before carbon removal during the preparation of silicon carbide powder During the preparation of silicon carbide powders of Examples 1-7 and Comparative Examples 1, 6-12 of the present invention, the mass change of the powders before and after carbon removal was measured, and the free carbon content of the silicon carbide powders obtained before carbon removal was calculated to characterize the reaction effect during the preparation of the silicon carbide powders of the present invention. The results are shown in Table 6.
[0079] Table 6
[0080] As shown in Table 6, the free carbon content in the silicon carbide powder of Examples 1-5 of the present invention before carbon removal is in the range of 0.67%-4.73%, among which the free carbon content in Example 5 is as low as 0.67%, which provides a basis for the subsequent smooth and rapid carbon removal and is also conducive to improving the purity of the silicon carbide powder. At the same time, the free carbon content in the silicon carbide powder before carbon removal also reflects the activity and effect of the carbon-silicon reaction of the present invention from the side.
[0081] By comparing Examples 1-3, it can be seen that when the organic nickel salt in Example 1 is disodium nickel ethylenediaminetetraacetate, the free carbon content in the silicon carbide powder before carbon exhaust is low, indicating that the catalytic activity of disodium nickel ethylenediaminetetraacetate is higher. On the basis of Example 1, Example 5 performs exhaust treatment on the dry powder before calcination, and the free carbon content is further reduced, indicating that the catalytic activity of the organic nickel salt is further improved after the exhaust treatment.
[0082] Compared with Example 1, Example 1 uses ordinary silicon dioxide. Compared with Example 5, Examples 6-12 change the preparation steps of silicon carbide powder. As a result, the free carbon content in the silicon carbide powder of Examples 1 and 6-12 before carbon removal increases to varying degrees, indicating that the reaction effect is deteriorated.
[0083] 4. Application of silicon carbide powder obtained by the present invention as ceramic material The silicon carbide powders prepared in Examples 1, 5-7 of the present invention and Comparative Examples 1, 6-12 were hot pressed and sintered, and their sintering properties were measured. The results are shown in Table 7. The hot pressing and sintering conditions are as follows: temperature of 1900°C, pressure of 30 MPa, and holding time of 40 min.
[0084] Table 7
[0085] As shown in Table 7, the sintering performance of the silicon carbide powders prepared in Examples 1, 5-7 of the present invention is good, the relative density is in the range of 99.4-99.8%, and the bending strength is in the range of 664-735 MN / m 2 In particular, the sintering performance of the silicon carbide powder obtained in Examples 5-7 is better.
[0086] Compared with Example 1, Comparative Example 1 uses ordinary silicon dioxide. Compared with Example 5, Comparative Examples 6-12 change the preparation steps of silicon carbide powder. As a result, the sintering performance of silicon carbide powder is deteriorated.
Claims
1. A method for preparing hollow nano-silica, characterized in that: The following steps are involved: A cationic compound is added to a nano-calcium carbonate suspension, the pH value of the solution is adjusted to 9-10, and then the solution is heated to 40-80°C and stirred for 10-60 minutes, and then a sodium silicate solution is slowly added under stirring conditions, aged for 2-5 hours, filtered, washed, dried at 100-120°C, and calcined at 300-600°C for 3-5 hours, and finally impurities are dissolved with hydrochloric acid, filtered, washed, and dried to obtain hollow nano-silica; the cationic compound is acetylglutamide aluminum.
2. The preparation method according to claim 1, characterized in that: The amount of the cationic compound added is 0.5-1.5% of the mass of the nano-calcium carbonate, the mass concentration of the nano-calcium carbonate suspension is 60-100 g / L, the mass concentration of silicon dioxide in the sodium silicate solution is 3-10%, and the mass ratio of the sodium silicate solution to the nano-calcium carbonate is 12-30% according to silicon dioxide / calcium carbonate.
3. A method for preparing silicon carbide powder, which is prepared by reacting a carbon source and a silicon source, characterized in that: The silicon source is hollow nano-silicon dioxide obtained by the method of claim 1, and the method for preparing the silicon carbide powder comprises the following steps: The hollow nano-silicon dioxide is dried to obtain dry powder, and the dry powder and carbon powder are calcined in an inert atmosphere to obtain silicon carbide powder after the calcination is completed; the crystal form of the silicon carbide powder is β-SiC.
4. The preparation method according to claim 3, characterized in that: An organic nickel salt is also added to the preparation method of the silicon carbide powder, and the preparation method of the silicon carbide powder comprises the following steps: The hollow nano-silicon dioxide is soaked in an organic nickel salt aqueous solution for 10-60 minutes, and then the water is evaporated to obtain a dry powder, and the dry powder and carbon powder are calcined in an inert atmosphere to obtain silicon carbide powder after the calcination is completed; the crystal form of the silicon carbide powder is β-SiC; The organic nickel salt is specifically disodium nickel ethylenediaminetetraacetate, nickel oxalate or nickel acetate.
5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of the hollow nano-silicon dioxide to the carbon powder is 1:(1-1.2) in terms of silicon / carbon; the calcination temperature is 1300-1600°C, the heating rate is 5-10°C / min, and the calcination time is 1-3h; the carbon removal temperature is 600-800°C, and the carbon removal time is 40-80min.
6. The preparation method according to claim 3 or 4, characterized in that: After carbon removal, the powder is also subjected to impurity removal, which is carried out by using any one or both of acid washing and alkaline washing. The acid is one or more of hydrochloric acid, hydrofluoric acid, sulfuric acid, and nitric acid, and the alkali is one or more of sodium hydroxide, potassium hydroxide, and ammonia water.
7. The preparation method according to claim 4, characterized in that: The organic nickel salt is disodium ethylenediaminetetraacetic acid nickel salt.
8. The preparation method according to claim 4, characterized in that: The molar ratio of the hollow nano-silicon dioxide to the organic nickel salt is 1:(0.02-0.1) in terms of silicon / nickel.
9. The preparation method according to claim 4, characterized in that: The preparation method further comprises exhausting the dry powder before calcination, wherein the exhausting is as follows: heating the dry powder to 200-400° C. at a rate of 6-15° C. / min in a flowing inert atmosphere and keeping the temperature for 5-30 minutes.
10. Use of silicon carbide powder obtained by the method according to claim 3 or 4 as ceramic material.
Citation Information
Patent Citations
Acetylglutamine compounds and their pharmaceutical compositions
CN102276496A
Method for preparing silicon carbide nano crystal whisker
CN110273183A
Method for preparing hollow microspheres based on dopamine modified calcium carbonate template
CN113697818A
Novel SiO2 carrier material and use in polyolefin catalyst and its preparing method
CN1781997A
Sic / c / sio2 composite powders fabricated by sol-gel process, and fabrication method of reaction bonded silicon carbide with high purity and high strength using them
KR1020100128777A